Influence of financial and financial literacy technology on financial management (to foodcourt MSME activities in Binjai city) - Wahyu Indah Sari; Wiwied Risdianto Putri; Suarika Diah Permata; M Gilang Dinata; Ridho Alansyah (Sean Institute, 2024)
This research aims to explore the impact of financial literacy and financial technology (fintech) on financial management in Micro, Small and Medium Enterprises (MSMEs) in Binjai City. Paying attention to the significant growth of MSMEs every year, the focus is to identify the low level of financial literacy among MSME players as well as the trend of society's shift towards financial technology. In its background, this journal highlights the importance of financial literacy for MSMEs and how advances in financial technology contribute to improved financial management. The research method is based on a descriptive quantitative approach, which uses questionnaires as a data collection technique and multiple regression analysis to examine the impact of financial literacy and financial technology on MSME financial management. The research results show that Financial Literacy has a positive and significant effect on the Financial Management of Binjai Foodcourt MSMEs . Financial Technology has a positive and significant influence on the Financial Management of Binjai Foodcourt MSMEs . Financial Literacy and Financial Technology have a positive and significant influence on the Financial Management of MSME Foodcourts in Binjai City.